Urgensi Kecerdasan Interpersonal Bagi Guru di Era Industri 4.0 - Ahmad Muthi’ Uddin; Anang Fathoni; Mahmud Samsuri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The rapid development of information technology in the industrial era 4.0 certainly contributes to shifting human activities in interacting and communicating. In the world of education, teachers need to synchronize learning in accordance with the characteristics of students in the industrial era 4.0. The main key in this synchronization arises in the competence of the teacher to be able to establish interpersonal relationships with learners, other educators, parents, and the educational community. So that the capacity of the teacher in interpersonal intelligence needs to be honed and adapted to his time. Therefore, the purpose of writing this article is to describe the urgency of interpersonal intelligence for teachers in the industrial era 4.0. The type of research used in this study is literature review research. The research approach used is in the form of sample characteristics systematically using sources in the form of books and articles. This research procedure consists of 5 stages, namely 1) determining the topic of study; 2) collect information from various sources; 3) classify references in accordance with the topic of study; 4) carry out the synthesis of relevant references; 5) write down the results of the synthesis. The results of this study show that 1) interpersonal intelligence is an important part for teachers as a basis for interaction between teachers and students, peers, parents, principals, policy makers, education observers, and the educational community; 2) interpersonal and intrapersonal intelligence has a relationship with one another; 3) communication of teachers and students in the industrial era 4.0. happening in classrooms and virtual spaces through social media; 4) teachers need to follow the development of information technology as a medium to learn and communicate with studentsThe rapid development of information technology in the industrial era 4.0 certainly contributes to shifting human activities in interacting and communicating. In the world of education, teachers need to synchronize learning in accordance with the characteristics of students in the industrial era 4.0. The main key in this synchronization arises in the competence of the teacher to be able to establish interpersonal relationships with learners, other educators, parents, and the educational community. So that the capacity of the teacher in interpersonal intelligence needs to be honed and adapted to his time. Therefore, the purpose of writing this article is to describe the urgency of interpersonal intelligence for teachers in the industrial era 4.0. The type of research used in this study is literature review research. The research approach used is in the form of sample characteristics systematically using sources in the form of books and articles. This research procedure consists of 5 stages, namely 1) determining the topic of study; 2) collect information from various sources; 3) classify references in accordance with the topic of study; 4) carry out the synthesis of relevant references; 5) write down the results of the synthesis. The results of this study show that 1) interpersonal intelligence is an important part for teachers as a basis for interaction between teachers and students, peers, parents, principals, policy makers, education observers, and the educational community; 2) interpersonal and intrapersonal intelligence has a relationship with one another; 3) communication of teachers and students in the industrial era 4.0. happening in classrooms and virtual spaces through social media; 4) teachers need to follow the development of information technology as a medium to learn and communicate with students